IMPLEMENTASI INTERNET OF THINGS (IoT) DALAM SISTEM IRIGASI TETES CERDAS: PROGRAM PELATIHAN DI SMK PP NEGERI MATARAM - Budiman, Djul Fikry; Misbahuddin, Misbahuddin; Iqbal, M. Syamsu; Rachman, A. Sjamsjiar; Akbar, Lalu Ahmad S. Irfan (Jurnal Abdi Insani, 2024)
Indonesia as an agricultural country has quite large agricultural potential and can contribute to the national economy. As an agricultural country, it means that the majority of the population in Indonesia depends on the agricultural sector for their livelihood. One of the government's calls to improve the performance of the agricultural sector is to encourage the younger generation, especially those at the Vocational High School (SMK) level, to get to know, study, and apply IoT products to support the Smart Farming concept. This call has encountered obstacles caused by SMK PP teachers, especially those who have competencies in food crop agribusiness, horticulture, plantations and seeds who do not understand agricultural technology. To overcome these obstacles, it is necessary to hold training and introduction to IoT-based technology that is implemented in the agricultural sector. The training provided begins with the concept of smart drip irrigation using IoT which is utilized in hydroponic plants. In the process of manually controlling water, farmers use watering time intervals without paying attention to soil moisture so that water supply is inefficient. With Internet Of Things (IoT) technology, automation of watering can be carried out so that the expected soil moisture can be maintained, without excessive water waste. The training was conducted by giving a lecture on the implementation of IoT in smart drip irrigation, followed by the introduction and assembly of IoT-based smart drip irrigation modules. The training conducted has provided new knowledge and understanding for students and teachers of SMK PP Negeri Mataram about the importance of technology such as IoT in managing agriculture. They hope that training like this can be continued and is expected to become one of the subjects in the SMK PP Negeri Mataram curriculum.